Cocoa Flavanol Intake and Biomarkers for Cardiometabolic Health: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 11 (28th September 2016) - Lin, Xiaochen; Zhang, Isabel; Li, Alina; Manson, JoAnn E; Sesso, Howard D; Wang, Lu; Liu, Simin
Abstract: Background: Cocoa flavanols may improve cardiometabolic health. Evidence from small short-term randomized clinical trials (RCTs) remains inconsistent, and large long-term RCTs testing the efficacy of cocoa flavanols are still lacking. Objective: We performed a systematic review and meta-analysis of RCTs to quantify the effect of cocoa flavanol intake on cardiometabolic biomarkers. Methods: We searched PubMed, Web of Science, and the Cochrane Library for RCTs that evaluated the effects of cocoa flavanols on biomarkers relevant to vascular disease pathways among adults. Data were extracted following a standardized protocol. We used DerSimonian and Laird random-effect models to compute the weighted mean differences (WMDs) and 95% CIs. We also examined potential modification by intervention duration, design, age, sex, comorbidities, and the form and amount of cocoa flavanol intake. Results: We included 19 RCTs that comprised 1131 participants, and the number of studies for a specific biomarker varied. The amount of cocoa flavanols ranged from 166 to 2110 mg/d, and intervention duration ranged from 2 to 52 wk. Cocoa flavanol intake significantly improved insulin sensitivity and lipid profile. The WMDs between treatment and placebo were −0.10 mmol/L (95% CI: −0.16, −0.04 mmol/L) for total triglycerides, 0.06 mmol/L (95% CI: 0.02, 0.09 mmol/L) for HDL cholesterol, −2.33 μIU/mL (95% CI: −3.47, −1.19 μIU/mL) for fasting insulin, −0.93 (95% CI: −1.31, −0.55) for the homeostatic model assessment of insulin resistance, 0.03 (95% CI: 0.01, 0.05) for the quantitative insulin sensitivity check index, 2.54 (95% CI: 0.63, 4.44) for the insulin sensitivity index, −0.83 mg/dL (95% CI: −0.88, −0.77 mg/dL) for C-reactive protein, and 85.6 ng/mL (95% CI: 16.0, 155 ng/mL) for vascular cell adhesion molecule 1. No significant associations were found for other biomarkers. None of the modifiers seemed to qualitatively modify the effects of cocoa flavanol intake. Conclusions: Our study suggests that cocoa flavanol intake has favorable effects on select cardiometabolic biomarkers among adults. These findings support the need for large long-term RCTs to assess whether cocoa flavanol intake reduces the risk of diabetes and cardiovascular events.